Pathogenic and antibiotic -resistant strains of Escherichia coli in wastewater effluents treated with UV radiation - Tavares, Rafael dos Santos (2021)
Antibiotic resistance jeopardizes the treatment of bacterial infections worldwide, with clinical and environmental compartments being recognized in its pandemic dissemination. Wastewater Treatment Plants (WWTPs) are notorious sources of antibiotic resistance into the aquatic systems and are thus considered a key node for containing the antibiotic resistance dissemination across the humanenvironmental microbiota axis. In this extent, disinfection of effluents before their discharge (e.g. by UV-C irradiation) is a promising strategy. However, some clinically relevant bacteria have been shown to survive such disinfection steps, though a knowledge gap exists in what regards their phenotypic and genotypic features. In this study we characterized a collection of clinically relevant extended-spectrum beta-lactamase-producing Escherichia coli isolated from an WWTP’s UV-C-irradiated effluent, aiming to identify putative human health risks associated with such effluents. Twenty-five strains of antibiotic-resistant, CTX-M-producing E. coli were genotyped (rep-PCR, Pulsed-Field Gel Electrophoresis, Multilocus Sequence Typing and Clermont phylogrouping), antibiotic-resistant genes (ARGs) and virulence genes (VGs) were PCR-detected, plasmids were analysed by enzymatic restriction and conjugal transfer was evaluated by mating assays. Biofilm, siderophore and haemolysin production, cytotoxicity and invasion into Vero cells and infection of Galleria mellonella larvae were phenotypically assessed. Illumina whole-genome sequencing and evaluation of persistence in freshwater microcosms was performed for 6 selected strains. Analysis of rep-PCR profiles separated strains into 2 major groups, including strains affiliated either with phylogroup B2-sgI (n=7 isolates) or with phylogroups A (n=16) and C (n=2); and further separated into 8 known STs, namely B2:ST131 (n=7), A:ST58 (n=1), A:ST155 (n=4), C:ST410 (n=2), A:ST453 (n=2), A:ST617 (n=2), A:ST744 (n=1) and A:ST1284 (n=3). Of 18 PCR-screened ARGs, 9 were detected (i.e. sul1, sul2, sul3, tet(A), tet(B), blaOXA-1-like, aacA4, aacA4-cr and qnrS1). No VGs were identified by PCR. Plasmid restriction indicated high diversity of plasmid profiles among strains and mating assays yielded cefotaxime-resistant transconjugants for 8 strains, two of which displaying a multi-drug resistant (MDR) phenotype. All strains were classified as cytotoxic (9 significantly more cytotoxic than the positive control), 10 of 21 strains were invasive (particularly B2:ST131 strains) and 10 selected isolates were pathogenic to larvae. Twenty-four and 7 of the 25 strains produced siderophores and haemolysins, respectively. Approximately 65% of the tested strains formed biofilms, 11 in two distinct experimental conditions. Genome analysis identified additional ARGs (e.g. catB3, strA, strB) and several VGs encoding toxins, siderophores, and colonizing, adhesion and invasion factors. Four of 6 strains were still detected by cultivation and/or qPCR after 28 days of incubation in freshwater microcosms, and resistance phenotypes remained unaltered. In this study, we confirmed WWTP’s UV-C-treated outflow as an input source of MDR and/or virulent E. coli strains, some probably capable of persisting in freshwater, and carrying conjugative antibiotic resistance plasmids. Hence, UVdisinfected wastewater may still represent a risk for human health and antibiotic stewardship, which implies a lack of efficiency of this treatment to remove pathogens from wastewater, compromising water reuse. More detailed evaluation of strains isolated from other wastewater effluents is urgent, in order to design new treatments or establish synergistic combinations that can mitigate the release of such bacteria into the environment.